Protective effects of the galectin-1 protein on in vivo and in vitro models of ocular inflammation - Zanon, Caroline de Freitas [UNESP]; Sonehara, Nathália Martins [UNESP]; Girol, Ana Paula [UNESP]; Gil, Cristiane Damas; Oliani, Sonia Maria [UNESP] (Molecular Vision, 2015)
Galectin-1 (Gal-1) is a β-galactoside-binding protein with diverse biological activities in the pathogenesis of inflammation but has been poorly investigated in terms of ocular inflammation. In the present study, we monitored the anti-inflammatory effects of Gal-1 using the in vivo rodent model of endotoxin-induced uveitis (EIU) and in vitro assays with human RPE (ARPE-19) cells. For this purpose, EIU was induced by subcutaneous sterile saline injection of 0.1 ml of lipopolysaccharide (LPS, 1 mg/Kg) in the rat paw, which was maintained under these conditions for 24 h. The therapeutic efficacy of recombinant Gal-1 (rGal-1) was tested in the EIU animals by intraperitoneal inoculation (3 µg/100 µl per animal) 15 min after the LPS injection. In vitro studies were performed using LPS-stimulated ARPE-19 cells (10 μg/ml) for 2, 8, 24 and 48 h, treated or not with rGal-1 (4 μg/ml) or dexamethasone (Dex, 1.0 μM). Gal-1 treatment attenuated the histopathological manifestation of EIU via the inhibition of polymorphonuclear cells (PMN) infiltration in the eye and by causing an imbalance in adhesion molecule expression and suppressing interleukin (IL)-1β, IL-6, and monocyte chemotactic protein-1 (MCP-1) productions. Immunohistochemical and western blotting analyses revealed significant upregulation of Gal-1 in the eyes induced by EIU after 24 h. In the retina, there was no difference in the Gal-1 expression, which was high in all groups, demonstrating its structural role in this region. To better understand the effects of Gal-1 in the retina, in vitro studies were performed using ARPE-19 cells. Ultrastructural immunocytochemical analyses showed decreased levels of endogenous Gal-1 in LPS-stimulated cells (24 h), while Dex treatment upregulated this protein. The protective effects of rGal-1 on LPS-stimulated cells were associated with the significant reduction of the release of cytokines (IL-8 and IL-6), similar to Dex treatment. Furthermore, rGal-1 and Dex inhibited cyclooxygenase-2 (COX-2) expression in LPS-stimulated cells, as shown by immunofluorescence. Overall, this study identified potential roles for Gal-1 in ocular inflammation, especially uveitis, and may lead to future therapeutic approaches.